A Voz da Raça, os ecos da educação: percepções sobre as permanências da herança cultural africana no Brasil - Dias, Ariadne Guimarães (2018)
This work aims to investigate the African presence on the newspaper “A Voz da Raça” (The Voice of the Race), a tabloid published by Frente Negra Brasileira (Brazilian Black Movement), from 1933 to 1937. To pursue this investigation was defined three steps: the key character, the black man who lived in São Paulo on the beginning of the XX century; the scene, the major ideas present on the black movements at that time; and the voice, the texts published by the followers of Frente Negra Brasileira. Achilles Mbembe's book (“Critique of Black Reason”) helps on the texts' analysis by a historical and social recuperation of black trajectory and his diaspora. Education, signalized by black activists as a possibility of social upgrade is investigated by different points: speech and practice versus State's model and alternatives paths. The analysis of Banto's words presence in the newspaper allows a perspective of African permanency in our lives. To summarize, the content stands out an undeniably black, African denunciation of abandonment, unemployment and the struggle for citizenship of Afro- descendants, albeit sometimes under a white and hegemonic discourse.(AU)